Bacterial chromosomal restriction endonuclease analysis of the homology of Bacteroides species. - Bradbury, W C (1985)
Chromosomal DNAs of selected Bacteroides organisms whose relatedness had been previously determined by "conventional" filter-annealing studies (J. L. Johnson, Int. J. Syst. Bacteriol. 28:245, 1978) were further analyzed by restriction endonuclease analysis coupled with the Southern hybridization procedure (E. M. Southern, J. Mol. Biol. 98:503, 1975). By comparing their EcoRI restriction fragment patterns in agarose gel electrophoresis, each Bacteroides strain could be clearly differentiated. As a simple and direct means for comparison purposes this method was particularly useful for differentiating genetically similar organisms such as Bacteroides strains of the same species which shared greater than 75% homology. In contrast, bacterial chromosomal restriction endonuclease analysis in conjunction with Southern hybridizations was most effectively used to determine the significance of low levels of homology (less than 24%) as this technique provided additional information on the nature and relative distribution of that homology when the areas of homology were displayed as reproducible bands in autoradiograms.